Diagnostic value of Krebs von den Lungen-6, a serological biomarker in interstitial lung disease - Cherukumalli Navya; Praveen Radhakrishnan; S. Yuvarajan; Reenaa Mohan (Journal of Current Research in Scientific Medicine)
Introduction: Krebs von den Lungen-6 (KL-6) biomarker has proven to be associated in the pathogenesis of interstitial lung disease (ILD). With this background, this study was done to find the diagnostic role of KL-6 in the ILD. This included establishing the role of KL-6 as a crucial diagnostic marker in early diagnosis, disease severity assessment, and its progression. Materials and Methods: After obtaining institutional ethical clearance, the present hospital-based cross-sectional study was done among patients with ILD (n = 56) above 18 years of age, attending the respiratory medicine department of a tertiary care teaching hospital in Puducherry. History, clinical examination, blood investigation for serology and biomarkers, lung function test, and biopsy were done. The study participants were assessed for KL-6, and analysis was done using SPSS (Version_24) software. Results: Among the 56 study participants, the subtypes of ILD include idiopathic pulmonary fibrosis (IPF) in connective tissue disorder (CTD)-ILD and others with a frequency of 23.18 and 15, respectively. The mean age of the study participants was 57.27 ± 12.95 years with 55.4% female predominance. The mean value of the KL-6 among the study participants was 485.18 ± 63.74 U/mL with a significantly higher mean in CTD-ILD (563.61 ± 21.88 U/mL) when compared to IPF (467.17 ± 27.46 U/mL) and other subtypes of ILD (426.67 ± 30.62 U/mL). Conclusion: Among the subgroups of ILD, KL-6 had a higher mean value in CTD-ILD when compared to IPF and other subgroups which were statistically significant. KL-6 can be considered the reliable indicator for the clinical diagnosis of ILD with a cutoff of ≥400 U/mL.